Formation of Adherent Negative Assessment of Media Neologisms - V. A. Kulikova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The features of the formation of an adherent negative assessment of neologism on the material of the headlines of electronic media are considered. The results of structural-semantic, contextual and pragmatic analysis of media neologisms expressing an adherent negative assessment are presented. The analysis of the main methods of forming an adherent negative assessment of neologisms under the influence of narrow (title context) and wide (context of an integral media product) verbal contexts, as well as under the influence of extra-linguistic conditions of use (communicative-pragmatic settings of the author, features of the subject of evaluation, specificity of the value system). It is concluded that the adherent negative evaluation of the neologisms is formed in the context due to the updating and intensification of the negative evaluation components of the semantics of the producing word, at the same time, due to the conditions of use, it is possible to de-intensify the estimated semantics of the structural components of the neologism, up to the neutralization of the evaluation of the neologism, as well as reversal (change of sign) of the assessment from positive to negative. Cases of the formation of adherent negative evaluation semantics in neologisms created on the basis of evaluation-neutral components are also analyzed. The practical significance of the study lies in the possibility of applying its results in journalistic practice, as well as in the practice of teaching university courses in morphemic, lexicology and special courses on the study of the language of the media, pragmalinguistics.